2012 International Conference on Systems and Informatics (ICSAI2012) 2012
DOI: 10.1109/icsai.2012.6223572
|View full text |Cite
|
Sign up to set email alerts
|

Resource modeling for Cyber Physical Systems

Abstract: The integration of physical systems and processes with networked computing has led to the emergence of a new generation of engineered systems, called Cyber-Physical Systems (CPS). The resources in these systems are critical, because without them timely and dependable CPS services in different contexts cannot be provided. This in turn requires a formal resource model integrated within a CPS service model. The resource model should include resource types and definition, resource utility, resource constraints, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…• Cyber-Physical Systems The physical information system is an effective bidirectional integration of the computing resources supported [75] by the network implementation of the CPS with the physical processes. It can provide real services in the face of real-time limitations [76], and based on continuous tracking, can automatically control a physical system that integrates several different communication systems and devices [77]. Some studies have shown the feasibility of CPS for real-time monitoring and visualization of CE data at construction sites [70,78].…”
Section: • Global Positioning Systemmentioning
confidence: 99%
“…• Cyber-Physical Systems The physical information system is an effective bidirectional integration of the computing resources supported [75] by the network implementation of the CPS with the physical processes. It can provide real services in the face of real-time limitations [76], and based on continuous tracking, can automatically control a physical system that integrates several different communication systems and devices [77]. Some studies have shown the feasibility of CPS for real-time monitoring and visualization of CE data at construction sites [70,78].…”
Section: • Global Positioning Systemmentioning
confidence: 99%
“…Subsequently, CPS realizes real-time bi-directional communication as well as real-time-based decision making and control in various sectors, such as manufacturing supply chain integration and quality control [28], real-time remote monitoring and treatments in healthcare [29], and smart grid management for reliability and efficiency of renewable energy supply [30], as well as building design and automation [31]. It has been recognized that CPS has possibilities to establish bi-directional information exchange and coordination between physical components and their virtual counterparts by visualizing physical components virtually and tracking information of the components in real-time within a virtual environment, without manually updating information of building components [32]. Indeed, CPS has been examined and confirmed for its adaptability for ever-changing situations of a building over its life-cycle [33].…”
Section: Bim-based Real-time Cyber-physical Data Exchangementioning
confidence: 99%
“…Distributed applications are also common which involve distributed management and /or distributed operations such as a power grid. Another feature of CPS is the ability to provide timely service in the face of real-time constraints (Wan and Alagar 2012).…”
Section: Key Features Of Cyber-physical Systems (Cps)mentioning
confidence: 99%